Pengaruh Telur Beromega-3 dan 6 Hasil Olahan terhadap Profil Lipid Darah Tikus Rattus norvegicus L. Normal dan Hiperkolesterolemia - D Hardini; T Yuwanta; . Supadmo; . Zuprizal (Faculty of Animal Science, Bogor Agricultural University, 2007)
The research was aimed to evaluate the change of trigliserida (TG), Low Density Lipoprotein (LDL) and High Density Lipoprotein (HDL) Rattus norvegicus L. blood fed fried and boiled egg yolk containing Polyunsaturated fatty acid, and omega-3- omega-6 with ideal ratio (1 : 5). Fifty two months old male of Rattus norvegicus L. separated in 2 groups; normal and hypercholesterolemia (blood cholesterol > 200 mg/dl). The rat placed in individual cage, fed 15 g/rat/day and drinking water ad lib. The ration was composed of 90% basal feed and 10% egg yolk of daily feed consumption (20% BW). Seven treatments of egg yolk were frying at 170 0C for 3 min (fried = GM), and 1 min (half fried = GSM) using deep fryer, oilless frying at = 70 0C for10 min (fried = TM), dan 6 min (half fried = TSM) using Teflon pan, and boiling at 100 0C for 10' (boiled = RM) dan 4 min (half boiled = RSM) using thermoregulator pan and a fresh omega egg as a control. Factorial 2 x 7 of completely randomized design was used for 4 weeks research period. The data were analyzed by ANOVA and Duncan's Multiple Range Test. The result showed that rat TG and LDL blood increased on the normal rat group and the GM egg showed the highest blood TG (98.71 mg/dl) and LDL (13.01 mg/dl). On hypercholesterolemia group of rat GM a highest TG bood, 121.04 mg/dl, respectively. In normal rat, the HDL blood tended to decrease, but that on hypercholesterolemia group increased, and GM egg showed the highest HDL (110.93 mg/dl). Half boiled egg was the best treatment for omega egg. Key words: omega-3, omega-6, fat profile, hypercholesterolemia